Pengaruh Value Added of Capital Employed, Value Added Human Capital dan Structural Capital Value Added terhadap Nilai Perusahaan F&B - Mentari Rizki Sawitri Pilomonu; Syamsul B. Biki; Mohammad Dimas Suronoto; Iklima Abdul Halid; Wayan Eka Ayu Noviantari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the influence of Value Added of Capital Employed (VACE), Value Added Human Capital (VAHC), and Structural Capital Value Added (SCVA) on firm value in Indonesia’s Food and Beverage (F&B) sector from 2022 to 2024. The research is driven by the growing significance of intellectual capital in boosting competitiveness and firm value, particularly in the rapidly transforming and digitalized F&B industry. A quantitative methodology was adopted, utilizing secondary data from the financial statements of F&B companies selected through purposive sampling. The data were analyzed using multiple linear regression, supplemented with classical assumption tests to validate the model. Key findings indicate that, collectively, the three independent variables significantly impact firm value. However, only SCVA demonstrates a positive and significant partial effect. The coefficient of determination (R²) of 26.1% suggests that the model accounts for a portion of the variation in firm value, leaving 73.9% attributable to external factors beyond the model’s scope. These results underscore the strategic importance of enhancing structural capital—through advancements in systems, technology, and organizational processes—as a means to elevate firm value in the F&B industry.